Dipturus amphispinus sp. nov., a new longsnout skate (Rajoidei: Rajidae) from the Philippines - Last, Peter R.; Alava, Moonyeen (Zootaxa, 2013)
A new long-snouted skate, Dipturus amphispinus sp. nov., is formally described based on material caught in the Sulu Sea and later acquired from fish markets of the central and southern Philippines. It differs from its congeners in the western North Pacific, apart from D. wuhanlingi (East and South China Seas), in having a variably-defined, parallel row of posterolaterally directed lumbar thorns, and well-developed scapular thorns on each side of the disc. However, the paired rows of lumbar thorns are better defined in Dipturus amphispinus sp. nov. than in D. wuhanlingi, and these species also differ in some aspects of their morphometrics, meristics and squamation. Dipturus amphispinus sp. nov. displays marked sexual dimorphism with adult males having a relatively broader mouth, much longer teeth, a relatively shorter snout, head and disc, a taller first dorsal fin, and a proportionally longer posterior pelvic-fin lobe and tail, than adult-sized females.